The idea of “normal risk” on put options related to investments in the energy sector - Martins-Costa, Judith (2023)
The objective of this article is to examine, through a functional methodology, the risks involved in put options related to investments in the energy sector, which presents several peculiarities. The study consists of delimiting which risks are or are not inserted in the normal scope of the contract. The option is examined from a functional perspective: whether its function is merely speculative or whether its purpose is to remove one of the partners. Considering the risks that exceed the normal range (alea normal), the possibility of contractual revision or termination is examined, analyzing the legal requirements contained in articles 317, 478 and 480 of the Brazilian Civil Code.